PENGEMBANGAN QUICK RESPONSE CODE INDONESIAN STANDARD MENGGUNAKAN METODE CUSTOMER PRESENTED MODE (QRIS-CPM). STUDI KASUS PT MTI - Mantik, Hari (Universitas Dirgantara Marsekal Suryadarma, 2021)
AbstractQR Code, or Quick Response Code not only created the evolution of barcodes from one dimension to two dimensions, and the ability to store large amounts of information, but also created changes in the lifestyle and payment methods of today's society. By using a digital wallet application (digital wallet), the shopping dimension becomes faster, easier, and more cash-less. This paper explores how to implement a QRIS (quick response indonesia standard) code scanning transaction as the basis for payment system service providers using digital wallet applications in general. One model of using QR, namely CPM (customer presented mode) is a QR method that is generated directly by customers through their devices. QRIS CPM makes it easy for customers to transact, and makes it easier for merchants to verify and settle. This study aims to show the results of the implementation of QRIS CPM in the development environment to ensure zero defects before being deployed to the production environment.Â Keywords: quick response Indonesian standard, customer presented mode, digital wallet.